2021
DOI: 10.3390/cells10123473
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Extracellular Vesicles from Bronchoalveolar Lavage Fluid and Plasma of Patients with Lung Lesions Using Fluorescence Nanoparticle Tracking Analysis

Abstract: The current lack of reliable methods for quantifying extracellular vesicles (EVs) isolated from complex biofluids significantly hinders translational applications in EV research. The recently developed fluorescence nanoparticle tracking analysis (FL-NTA) allows for the detection of EV-associated proteins, enabling EV content determination. In this study, we present the first comprehensive phenotyping of bronchopulmonary lavage fluid (BALF)-derived EVs from non-small cell lung cancer (NSCLC) patients using clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…At present, there are no EV extraction methods that could purify biological fluid samples from all cell debris and proteins ( 35 ) and, in our study, TEM, CLSM, and WB analyses showed potential sample contamination. EV surface proteins are attached to the EV membrane with a smooth diffuse manner that forms a protein corona for the EV.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…At present, there are no EV extraction methods that could purify biological fluid samples from all cell debris and proteins ( 35 ) and, in our study, TEM, CLSM, and WB analyses showed potential sample contamination. EV surface proteins are attached to the EV membrane with a smooth diffuse manner that forms a protein corona for the EV.…”
Section: Discussionmentioning
confidence: 59%
“…The lack of a universal EV isolation protocol is a key challenge for EV research. Earlier studies have shown successful isolation of EVs from human and mouse BALF with ultrafiltration and ultracentrifugation (15,(35)(36)(37). Recently, SEC has become a popular method for isolating EVs because of the relatively pure and intact EVs that it can produce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of EVs in peripheral blood is higher than that in BALF, but the source is complex, and the heterogeneity is strong [29]; plasma also contains high concentrations of proteins and lipoproteins, making the puri cation of EVs di cult [30,31]. However, BALF does not have high lipoprotein and protein contents.…”
Section: Discussionmentioning
confidence: 99%
“…Except for the apoptotic bodies, all EVs are released into circulation by living cells, either by direct budding of the plasma membrane (oncosomes and microvesicles) or via the endosomal pathway (exosomes) [ 200 , 202 ]. EVs can be found in many biological fluids, including blood [ 203 ], amniotic fluid [ 204 ], urine [ 205 ], CSF [ 206 ], breast milk [ 207 ], saliva [ 208 ], ascites [ 209 ], tears [ 210 ], semen [ 211 ], bronchoalveolar lavage fluid [ 212 ], and in the conditioned media of cultured cells [ 213 ].…”
Section: Ddpcr-based Liquid Biopsies For Skin Cancer Monitoring and P...mentioning
confidence: 99%